Foliar-Applied Silicon in Sorghum (Sorghum bicolor L.) Alleviate Zinc Deficiency - de Farias Guedes, Victor Hugo [UNESP] (2020)
Foliar-applied silicon may reduce the damage caused by zinc (Zn) deficiency in plants. While adding silicon (Si) and Zn to the solution may increase foliar fertilization efficiency, Si effects on sorghum plants are not known yet. Therefore, this study investigates how four different Zn chelate concentrations, with and without Si, applied via leaf, affect sorghum nutrition and development. The experimental design consisted of a 4 × 2 factorial scheme with four Zn-EDTA (0, 0.60, 1.20, and 1.80 g L−1) and two Si (control and 0.50 g L−1) concentrations applied via leaf, and five replicates. The evaluated parameters were Zn and Si accumulation, Zn use efficiency, cell electrolyte leakage, as well as chlorophyll, carotenoids, protein, and dry matter content. In Zn deficient plants, foliar-applied Si increased Zn accumulation, photosynthetic pigments, shoot and root dry matter while decreasing cell leakage. Zn chelates with added foliar-applied Si increased Zn accumulation, photosynthetic pigments, protein, and root dry matter. In conclusion, foliar spraying of Si alleviates Zn deficiency in sorghum plants and, therefore, adding Si to the Zn solution is agronomically feasible.